Hydrothermal Synthesis and Magnetic Properties of Zn/Mn Oxides Nano Particles - Izabela Kuryliszyn-Kudelska; Witold Dobrowolski; Monika Arciszewska; Branka Hadžić; Nebojsa Romčević; Maja Romčević; Daniel Sibera; Urszula Narkiewicz (Magnetochemistry, 2023)
The aim of this study was to investigate the magnetic properties of mixed nanocrystalline Zn/manganese oxide compounds synthesized by a hydrothermal method. These compounds are designed as (ZnO)1−n(MnO)n, where index n ranges from 0.05 to 0.60. The results of magnetic measurements, including AC magnetic susceptibility as a function of temperature (up to 160 K) and frequency (from 7 Hz up to 9970 Hz), as well as DC magnetization in magnetic fields up to 9 T and temperature up to 50 K, are reported. We observed various types of magnetic behavior depending on the nominal weight content of MnO. Samples with a low nominal content (up to n = 0.10) of MnO exhibited Curie–Weiss behavior at higher temperatures. For samples with high nominal weight contribution (from n = 0.30 to 0.60), spin-glass-like or/and weak ferromagnetic behavior is observed.